ANALISA RAP DAN RAB MELALUI PERHITUNGAN HARGA UPAH DAN BAHAN PEMBESIAN KOLOM 25/25 TERHADAP PELAKSANAAN PEKERJAAN PEMBANGUNAN - Asep Permana; Adi Subandi; Yusup Yulianto (MESA (Teknik Mesin, Teknik Elektro, Teknik Sipil, Teknik Arsitektur), 2022)
Doing an accurate estimate is very necessary before a project starts. The goal is to get a small cost and find out how much profit will be obtained, fast time and good quality so that the project runs without a hitch. Cost estimation has important elements, namely the coefficient value, worker wages, material prices and the volume of the work. However, there are often problems in calculating the price due to the coefficient and volume values . Sothis study was conducted to find out how much profit will be obtained from the comparative analysis of the RAB and RAP, the data is taken from 2 studies that discuss the work of 25/25 column ironing. Then processing RAB and RAP data from the overall coefficient of labor, labor wages, material coefficients, material prices, and volume. This is to find out how much profit from the 25/25 column construction project the Ministry of Religion Phase II will get.